Integrasi Nilai Pancasila Dalam Kepemimpinan Kepala Sekolah di SMAN 2 Ponorogo - Pamungkas, Wahyu Aji; Sulton (JPK (Jurnal Pancasila dan Kewarganegaraan), 2026)
This research aims to analyze the integration of Pancasila values in the leadership of the Principal at SMAN 2 Ponorogo. Amidst the challenges of moral degradation and national identity crisis, the role of the school principal as a moral institution is crucial in internalizing national ideology into school culture. This research uses a descriptive qualitative approach with data collection through in-depth interviews, participatory observation, and documentation studies. The research results show that the integration of Pancasila values is carried out through a leadership-by-example strategy which includes three main dimensions: (1) The Divinity Dimension through consistent religious habituation as an ethical foundation; (2) The Democracy Dimension through participatory deliberation and consensus management; and (3) The Social Justice Dimension through the "Humanitarian Laboratory" program in the form of social service. The research conclusion emphasizes that the "leadership with heart" approach and the principal's position as a "second parent" successfully created a harmonious school ecosystem and improved student integrity. This model is relevant as a reference in implementing the Pancasila Student Profile in the digital era.